2021
DOI: 10.1111/jpc.15285
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 pandemic on the well‐being of children with neurodevelopmental disabilities and their parents

Abstract: Aims To examine the impact of COVID‐19 pandemic on child mental health and socio‐emotional and physical well‐being (including sleep, diet, exercise, use of electronic media; care giver perceptions of symptoms of child neurodevelopmental disability [NDD] and comorbidities), and care giver mental health and well‐being, social support and service use. Methods An online cross‐sectional self‐report survey was distributed via disability service providers and support groups. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
199
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(218 citation statements)
references
References 18 publications
14
199
1
4
Order By: Relevance
“…This review highlights the psychological and social consequences of the pandemic for people with intellectual disability who have stopped participating in their communities and have had their routines interrupted during lockdown/restrictions for a prolonged period [ 59 , 60 , 61 ] and access to education, health, vocation and mental health service disrupted [ 50 , 62 ]. In addition, many have found it difficult to understand COVID-19 and self-regulate their behaviour, creating a risk of behaviours that challenge which negatively affect the emotional well-being and quality-of-life of the person [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…This review highlights the psychological and social consequences of the pandemic for people with intellectual disability who have stopped participating in their communities and have had their routines interrupted during lockdown/restrictions for a prolonged period [ 59 , 60 , 61 ] and access to education, health, vocation and mental health service disrupted [ 50 , 62 ]. In addition, many have found it difficult to understand COVID-19 and self-regulate their behaviour, creating a risk of behaviours that challenge which negatively affect the emotional well-being and quality-of-life of the person [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Families have been asked to take care of online special education and therapies, which have further increased parents' load and psychological distress, with negative effects on children [20,21]. All these factors together put children at greater risk of relapse or worsening of mental health issues [28][29][30][31]. According to a cross-sectional U.K. study, during the COVID-19 emergency children with NDD (aged 4-15 years) had worse emotional symptoms compared to a similar pre-COVID-19 mental health cohort and a higher prevalence of emotional symptoms and conduct problems compared to neurotypical controls [32].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies addressed specific pediatric populations including those diagnosed with eating disorders, 14,15,16,17,18 ADHD, 19 autism, 19,20,21,22,23 other severe mental health concerns, 24,25,26,27,28,29,30,31,32,33,34 and chronic medical conditions including epilepsy. 35,36 Among individuals with eating disorders, worsening symptoms (e.g., increased distress, binge eating) were reported, signaling the need for additional and/or sustained psychological care.…”
Section: Special Populationsmentioning
confidence: 99%
“…22 However, other studies of children with autism reported several challenges (e.g., decreased follow up, potential worsening of symptoms) during telehealth. 20,21 Other investigations of youth with complex disabilities reported increased mental health concerns among children and caregivers, 25 as well as mixed to low satisfaction with virtual care (e.g., decreased access to care, perceived as a poor fit for their child). 25,26 More than a quarter of caregivers reported inadequate support from those who addressed mental health challenges (e.g., in schools or healthcare settings).…”
Section: Special Populationsmentioning
confidence: 99%
See 1 more Smart Citation